Exposure to the immunomodulatory chemical triclosan differentially impacts immune cell populations in the skin of haired (BALB/c) and hairless (SKH1) mice. (2022) - Baur, Rachel; Shane, Hillary L.; Weatherly, Lisa M.; Lukomska, Ewa; Kashon, Michael; Anderson, Stacey E.
Abstract: Workers across every occupational sector have the potential to be exposed to a wide variety of chemicals, and the skin is a primary route of exposure. Furthermore, exposure to certain chemicals has been linked to inflammatory and allergic diseases. Thus, understanding the immune responses to chemical exposures on the skin and the potential for inflammation and sensitization is needed to improve worker safety and health. Responses in the skin microenvironment impact the potential for sensitization; these responses may include proinflammatory cytokines, inflammasome activation, barrier integrity, skin microbiota, and the presence of immune cells. Selection of specific mouse strains to evaluate skin effects, such as haired (BALB/c) or hairless (SKH1) mice, varies dependent on experimental design and needs of a study. However, dermal chemical exposure may impact reactions in the skin differently depending on the strain of mouse. Additionally, there is a need for established methods to evaluate immune responses in the skin. In this study, exposure to the immunomodulatory chemical triclosan was evaluated in two mouse models using immunophenotyping by flow cytometry and gene expression analysis. BALB/c mice exposed to triclosan (2%) had a higher number and frequency of neutrophils and lower number and frequency of dendritic cells in the skin compared to controls. Although these changes were not observed in SKH1 mice, SKH1 mice exposed to triclosan had a higher number and frequency of type 2 innate lymphoid cells in the skin. Taken together, these results demonstrate that exposure to an immunomodulatory chemical, triclosan, differentially impacts immune cell populations in the skin of haired and hairless mice. Additionally, the flow cytometry panel reported in this manuscript, in combination with gene expression analysis, may be useful in future studies to better evaluate the effect of chemical exposures on the skin immune response. These findings may be important to consider during strain selection, experimental design, and result interpretation of chemical exposures on the skin. Graphical Abstract: ga1 Highlights: Exposure to triclosan differentially impacted immune cells between mouse strains. Mouse strain is important to consider in dermal chemical exposure studies. Flow cytometry panels can be used to characterize potential dermal immune effects.